Entrepreneurial competencies in Potosina women: a qualitative perspective. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
The promotion of female entrepreneurship is crucial not only for its economic contribution, but also for its social impact by reducing gender inequalities and empowering women in the economic sphere. This article aims to contextualize and highlight the entrepreneurial competencies of women in San Luis Potosí, as well as the challenges and obstacles they face. The research adopts a qualitative, descriptive and cross-sectional approach, using semi-structured interviews with 32 women entrepreneurs to collect data on the characteristics of their businesses and the most significant aspects of their entrepreneurial activity. Among the main findings was the maturity of the businesses, many of which have been in business for more than five years. The entrepreneurs have learned to balance their roles as mothers and entrepreneurs. However, the main driver of their entrepreneurship is the need for self-employment due to the scarcity of job opportunities in their municipalities, which reflects the socio-cultural conditions of their environment. The leadership developed through their businesses is shown to offer solutions and alternatives to local problems and needs. The outstanding skills of these women include multitasking ability, independence to move forward and willingness to share knowledge with others.
Keywords: female entrepreneurship; entrepreneurial capabilities; socioeconomic characteristics